Impact of SPR biosensor assay configuration on antibody: Neonatal Fc receptor binding data. Issue 2 (17th February 2017) - Wang, Xiangdan; McKay, Patrick; Yee, Liliana T.; Dutina, George; Hass, Philip E.; Nijem, Ihsan; Allison, David; Cowan, Kyra J.; Lin, Kevin; Quarmby, Valerie; Yang, Jihong
ABSTRACT: Binding interactions with the neonatal Fc receptor (FcRn) are one determinant of pharmacokinetic properties of recombinant human monoclonal antibody (rhumAb) therapeutics, and a conserved binding motif in the crystallizable fragment (Fc) region of IgG molecules interacts with FcRn. Surface plasmon resonance (SPR) biosensor assays are often used to characterize interactions between FcRn and rhumAb therapeutics. In such assays, generally either the rhumAb (format 1) or the FcRn protein (format 2) is immobilized on a biosensor chip. However, because evidence suggests that, in some cases, the variable domains of a rhumAb may also affect FcRn binding, we evaluated the effect of SPR assay configuration on binding data. We sought to assess FcRn binding properties of 2 rhumAbs (rhumAb1 and rhumAb2) to FcRn proteins using these 2 biosensor assay formats. The two rhumAbs have greater than 99% sequence identity in the Fc domain but differ in their Fab regions. rhumAb2 contains a positively charged patch in the variable domain that is absent in rhumAb1. Our results showed that binding of rhumAb1 to FcRn was independent of biosensor assay configuration, while binding of rhumAb2 to FcRn was highly SPR assay configuration dependent. Further investigations revealed that the format dependency of rhumAb2-FcRn binding is linked to the basic residues that form a positively charged patch in the variable domain of rhumAb2. Our work highlights the importance of analyzing rhumAb-FcRn binding interactions using 2 alternate SPR biosensor assay configurations. This approach may also provide a simple way to identify the potential for non-Fc-driven FcRn binding interactions in otherwise typical IgGs.